DAMPAK INSOMNIA TERHADAP KONDISI EMOSIONAL DAN KOGNITIF INDIVIDU - Setya Vahreza, Ayudhiar; Purnomosidi, Faqih; Rachmawati Musslifah, Anniez (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Individuals must get adequate sleep to remain physically and mentally healthy. However, work demands, academic pressure, and contemporary lifestyles cause many people to experience sleep disorders, one of which is insomnia. The impact of insomnia on a person's emotional and cognitive health is the subject of this study. Seven adult informants who experienced insomnia, both temporary and chronic, participated in this study, which was conducted using a qualitative and phenomenological approach. Data were collected through observation and in-depth interviews. In this study, insomnia is considered a serious psychophysiological disorder that has a major impact on a person's emotional balance and thinking abilities. Therefore, the treatment of insomnia must be accompanied by efforts to manage stress, control emotions, and support cognitive function. It is hoped that more people will realize the importance of good sleep for mental health and overall quality of life.